Review on Application of Nucleic Acid Amplification Techniques in Pharmaceutical Products Analysis - Mohammad Saleh Al-Aboody (Journal of Applied Pharmaceutical Science, 2015)
The aim of this study was to describe application of molecular diagnostic tests based on nucleic acid amplification technologies (NAATs) in pharmaceutical product analysis. NAAT have become widely established in clinical microbiology laboratories in recent years, as well as in quality control (QC) laboratories for food testing, and lately introduced to the pharmaceutical QC laboratories. The number of available nucleic acid and gene amplification-based rapid microbiological methods has increased over the last few years, and for good reason. When compare to standard culture based methods, NAAT provide a rapid, an accurate and reliable means for detecting specific microorganisms of interest, especially in pharmaceutical dosage forms that are required to be free of objectionable or specified pharmacopeial organisms. This article discussed about the different types of nucleic acid amplification techniques and methods available to pharmaceutical microbiologists working on quality control of pharmaceutical products and develop some awareness among other pharmaceutical scientists. This review also highlights limitations of these methods applied in industrial setup.
Keywords: Nucleic acid amplification techniques, Polymerase chain reaction, Pharmaceutical products, rapid methods, ATP.